SECOND NAVAL FLEET COMMAND DISINFOLAHTA INFORMATION SYSTEM NETWORK COMMUNICATION PROCEDURE FOR SUPPORTING THE NAVAL TASK - Adi Widodo; Chairul Imron; Sutrisno Sutrisno; Zainal Syahlan (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
Disinfolahta’s second naval fleet command has the Main task of assisting with the field of development, data collection, and processing as well as presenting information, research, and development within the Koarmada II environment and acting as an information technology service center. Telegraphic communication radio within the Indonesian Navy is used for long-distance communication between ships, aircraft, and international shore radio. RTG Telegraphic communication radio uses international Morse signs, Q codes, and Z code procedural signs to convey information or news. The application of Radio Communication Telegraphy is very vulnerable to information theft. Important information conveyed from ship to ship, ship to aircraft, or to shore radio or vice versa can be accessed publicly. Information system security defense at Disinfolahta Koarmada II has not shown a level of efficiency and effectiveness, due to the absence of a special section in the field of information system security issues related to data transactions in communication networks. Improvement or improvement of information security is needed which plays a role in maintaining the confidentiality of information. Increasing the security and confidentiality of information is very necessary so that important information that is distributed is not known by unauthorized parties. This study plans a communication protocol scenario using the Mavlink and AX2.5 communication protocols. Each scenario will be run using a simulation to get network performance. The results of network performance measurements will be modeled using a dynamic system to get the best communication protocol as a proposal in order to improve the information security system at the Second naval fleet command. Keywords: RTG, Mavlink, AX2.5, network performance, communication protocols